Exploring the Mediating Effect of Conscious Health Habits Among Factors Influencing Health App Adoption Users in India - Jawahar, Vidhya; Venkatesh, Shanthi; William Robert, P.; Ruban Christopher, A.; Nithya, A. R. (Indian Journal of Information Sources and Services, 2025)
Purpose: This study explores the mediating role of conscious health habits in influencing the adoption of health apps among users in India. Design/methodology/approach: This research study focuses on a diverse sample of users in India, utilizing a comprehensive survey-based methodology to explore the intricate relationship between the usage of health applications and the formation of conscious health habits. After a rigorous screening process, a total of 185 respondents’ data was taken to test the relationship between variables. PLS-SEM 4.0 was employed to validate the research hypothesis. Findings: It is found that health benefits, convenience, and social factors influence health app adoption. Moreover, conscious health habits – such as regular exercise, mindful eating, and proactive health monitoring mediate the app users towards technological adoption. Research Limitations/Implications: With growing concerns over lifestyle diseases and the demand for personalized healthcare, understanding factors that drive health app adoption is crucial. The implications of this study highlight the importance of integrating behavioral health interventions in app design to boost engagement. For future research, there is potential to explore longitudinal impacts of health app usage on sustained lifestyle changes. However, the study brings a gap among diverse demographic and geographic groups, changing preferences to assess broader applicability. Originality/Value: This study provides valuable insights into the managerial perspectives that influence future decision-making processes within app development companies, focusing on strategic considerations rather than the technical functionalities of the applications.